HUBUNGAN KARAKTERISTIK IBU, POLA ASUH DAN PEMBERIAN IMUNISASI DASAR TERHADAP STATUS GIZI ANAK USIA 12-24 BULAN (STUDI DI WILAYAH KERJA PUSKESMAS KEDUNGMUNDU KOTA SEMARANG TAHUN 2017) - Distia Hayyudini; Suyatno Suyatno; Yudhy Dharmawan (Fakultas Kesehatan Masyarakat Universitas Diponegoro, 2017)
Nutritional issues are the major public health problem in Indonesia. Prevalence of toddler’s nutritional status based on Weight/Age in Central Java was 3,54% nutrient deficiency, and 0,4% was malnutrition, in Semarang City there were 39 cases of malnutrition and in Kedungmundu Health Center there were 25 cases of nutrient deficiency and 3 cases of malnutrition. The purpose of the study was to analyze the correlation of mother’s characteristics, parenting and giving basic immunization with nutritional status of 12-24 months children in the working area of Kedungmundu Health Center. This was an explanatory study with cross sectional design. Population of this study were mothers who had 12-24 months children with the total of 1.692 people and total samples were 91 people who were selected using simple random sampling. Data was analyzed using partial correlation test (p<0,05). The results showed that the biggest precentage of the respondents were in 20-35 years old (95,6%), educated for > 9 years (65,9%), had not poor social economy (83,5%), had a good parenting skill (56%), had children with incomplete immunizational status (52,7%) and had children with normal nutritional status (84,6%). Mother’s age with parenting were not correlated (p = 0,513), mother’s education with parenting were correlated (p = 0,014), economy status with parenting were correlated (p = 0,008), mother’s age with basic immunization status were not correlated (p = 0,629), mother’s education with basic immunization status were correlated (p = 0,000), economy status with basic immunization status were correlated (p = 0,023), parenting wth nutritional status were not correlated (p = 0,995), basic immunization status with nutritional status were not correlated (p = 0,880). Mother’s age were not correlated (p = 0,612), mother’s education were correlated (p = 0,018), economy status were not correlated (p= 0,355) with nutritional status through parenting control. Mother’s age were not correlated (p= 0,618), mother’s education were correlated (p = 0,012), economy status were not correlated (p = 0,340) with nutritional status through basic immunization control.